Role of IDO and TDO in Cancers and Related Diseases and the Therapeutic Implications - Ye, Zixiang (J Cancer, 2019)
Kynurenine (Kyn) pathway is a significant metabolic pathway of tryptophan (Trp). The metabolites of the Kyn pathway are closely correlated with numerous diseases. Two main enzymes, indoleamine-2,3-dioxygenase (IDO) and tryptophan-2,3-dioxygenase (TDO or TDO2), regulate the first and rate-limiting step of the Kyn pathway. These enzymes are directly or indirectly involved in various diseases, including inflammatory diseases, cancer, diabetes, and mental disorders. Presently, an increasing number of potential mechanisms have been revealed. In the present review, we depict the structure of IDO and TDO and explicate their functions in various diseases to facilitate a better understanding of them and to indicate new therapeutic plans to target them. Moreover, we summarize the inhibitors of IDO/TDO that are currently under development and their efficacy in the treatment of cancer and other diseases.